Conjugation of antibody with temperature-responsive polymer via in situ click reaction to enable biomarker enrichment for increased diagnostic sensitivity. (27th April 2021) - Hironaka, Keita; Yoshihara, Erika; Nabil, Ahmed; Lai, James J.; Kikuchi, Akihiko; Ebara, Mitsuhiro
Abstract : A portable, fast, simple, and sensitive strategy for biomarker enrichment was developed based on immune affinity and temperature-responsive smart polymers concepts to avoid the misdiagnosis that normally happens, especially with commercially available LFIA. Abstract : Early diagnosis of infectious diseases is one of the current prevalent challenges, especially in low and limited resource settings where simple, fast, portable, cheap, and sensitive diagnostic approaches are needed. Lateral flow immunoassay (LFIA) is a common, rapid screening assay. However, the low assay sensitivity limits the utility of LFIA for specimens with low pathogenic loads (early infection stages). Antibodies conjugated with stimulus-responsive polymers have been previously utilized to improve assay sensitivity for detection of biomarkers at low concentrations. However, the loss of antibody affinity after polymer conjugation remains a significant challenge. In this study, we developed poly( N -isopropylacrylamide- co-N -(2-hydroxyisopropyl)acrylamide- co -strained alkyne-isopropylacrylamide), a novel polymer for biomarker enrichment, by polymer conjugation after antibody–antigen recognition. We employed and promoted the click chemistry in situ, to facilitate highly specific conjugation between novel temperature-responsive polymers and antibody–antigen complexes. This method could suppress the decrease in the binding constant associated with polymer conjugation (>20-fold). The conjugation was successfully demonstrated in body fluids such as urine and saliva. We achieved >5-fold antigen enrichment via thermal precipitation by conjugating polymers to the antibodies after antigen recognition. Concentrated biomarkers resulted in improved LFIA detection. This approach can potentially be utilized to improve diagnostic tests for infectious diseases in low and limited resource settings.